Towards a Discussion of Support to Urban Transport Development in India - Mitric, Slobodan; Chatterton, Isabel (World Bank, Washington, DC, 2018)
The purpose of this policy note is to respond to the request from the Government of India for the World Bank to provide support to the development of the urban transport agenda in India and to provide lending support. During the discussions between the World Bank and the Government of India represented by the Ministry of Finance, the Department of Economic Affairs (DEA) agreed on a three year program of support 2005-2008 reflected in the World Bank's Country Strategy for India September 15, 2004. Support is currently reflected in the operations program as an urban transport project under consideration and as a policy note as part of the non-lending services. In conjunction with these operations support to urban roads are included in Chennai under the Tamil Nadu Third Urban Development Project and in Bangalore under the Karnataka Municipal Reform Project.